Profile of Energy Consumption Levels, Protein, Infectious Diseases, and Nutritional Status of Toddlers at Abepura Community Health Center, Kota Baru Urban Village - Rosmin M. Tingginehe; Suriani Korwa; Samuel Piter Irab; Nova F. Rumaropen; Yohanis M. Mandosir; Sarni Rante Allo Bela; Evi Sinaga; Budi Kristanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nutritional status is a measure of the success of fulfilling nutrition in children which is shown through the achievement of weight for age. The nutritional status of toddlers is very significant as a starting point for physical certainty in adulthood. This research method is quantitative research using a descriptive approach. The research involved a population of 420 toddlers and 111 samples of toddlers at the Abepura Community Health Center, Kota Baru Urban Village, taken using the purposive sampling method. The research results showed that the dominant level of energy consumption among respondents was in the good category, 80 respondents (72.1%), while in the poor category there were 31 (27.9%).